Oxidation of ethyl benzene and diphenyl methane over ordered mesoporous M-MCM-41 (M = Ti, V, Cr): synthesis, characterization and structure-activity correlations - Jha, Ratnesh Kumar; Shylesh, S.; Bhoware, Shrikant S.; Singh, A. P. (Microporous and Mesoporous Materials, 2006)
Transition metals (M = Ti, V, Cr) were incorporated into the MCM-41 framework by surfactant-assisted direct hydrothermal (DHT) methods and were characterized in detail by XRD, N-2 adsorption-desorption, TG-DTG/DTA, SEM/TEM, DR UV-Vis, XPS and EPR. The structural regularity as well as the textural properties of the M-MCM-41 materials was confirmed by XRD, TEM and adsorption-desorption techniques. Nature of metal species and the percentage of framework as well as extra framework metal sites in the MCM-41 matrix are discussed in detail by various spectroscopic techniques. The catalytic activity as well as the selectivity of the M-MCM-41 catalysts were explored in the one-step liquid-phase oxidation reaction of ethyl benzene and diphenyl methane. Reaction data showed that the oxidation activity is more when H2O2 was used an oxidant, acetonitrile as solvent and V-MCM-41 as catalyst. However, the selectivity towards the desired keto derivatives (ethyl benzene to acetophenone and diphenyl methane to benzophenone) follows the order, Ti-MCM-41 > V-MCM-41 > Cr-MCM-41. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: diphenyl methane; Ethyl benzene; MCM-41; Oxidation

One step synthesis of chromium-containing periodic mesoporous organosilicas and their catalytic activity in the oxidation of cyclohexane - Shylesh, S.; Srilakshmi, Ch.; Singh, A. P.; Anderson, B. G. (Microporous and Mesoporous Materials, 2007)
Chromium-containing ethane-bridged hybrid mesoporous materials (Cr-PMO) with uniform hexagonal arrangement were synthesized by two different synthesis routes using 1,2-bis(triethoxysilyl)ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts (ATMA) as surfactants. Powder X-ray diffraction, TEM, N-2 adsorption-desorption, FT-IR, in situ FT-Raman, UV-ViS, XPS, Si-29 MAS NMR and C-13 CP MAS NMR were used to probe the mesoporous structure and the nature of chromium sites in the hybrid catalyst matrix. PXRD, TEM and N-2 adsorption-desorption analysis showed that the original hexagonal structure of the materials is maintained after chromium substitution, while FT-Raman, UV-Vis and XPS analysis showed that chromium atoms exist in a highly dispersed state. The catalytic performance of the chromium-containing hybrid samples was tested in the liquid-phase oxidation of cyclohexane with aqueous hydrogen peroxide (H2O2) and non-aqueous tert-butylhydroperoxide (TBHP) as oxidants. The hybrid materials exhibited better catalytic activities and were more stable than the conventional Cr-MCM-41 catalyst. The higher catalytic activity of the new chromium-containing molecular sieves is attributed to the improved hydrophobicity of the materials and to the complementary structural features that facilitates the accessibility of cyclohexane to the active framework chromium sites. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Cr-MCM-41; Cr-PMO; Cyclohexane; hybrid mesoporous materials; Oxidation